European Parliament environmental amendments, 1999-2009 - Burns, Charlotte (UK Data Service, 2010)
The European Union (EU) is one of the principal sources of progressive environmental policy in Europe and the European Parliament (EP) is one of the three key policy-making actors in the EU. It is the only directly elected EU institution, and it has the power to amend and reject legislation that affects up to 500,000,000 people. Hence, the EP's actions have a daily effect upon the lives of EU citizens, and upon environmental policy output. Whilst the EP has an established reputation as a positive force for environmental change in the EU, there has been no comprehensive study of how the Parliament behaves when dealing with environmental legislation. Indeed, existing studies of the EP's environmental record tend to be skewed by a focus upon the behaviour of its environment committee, rather than the Parliament's plenary as a whole, and to analyse individual case studies of legislation where the EP has made a positive contribution. This study rectifies this imbalance by evaluating all EP plenary amendments addressed to environmental legislation adopted under co-decision over a ten year period. The researchers have analysed 7,094 amendments adopted by the EP's plenary to 113 pieces of environmental legislation between 1999 and 2009. Each amendment has been awarded a score for its environmental ambition, its legislative importance, and the degree to which it was adopted by the European Commission and European Council.